Chloride binding by calcined layered double hydroxides and alumina-rich cementitious materials in mortar mixed with seawater and sea sand. (26th July 2021) - Li, Shicai; Jin, Zuquan; Yu, Yong
Graphical abstract: Highlights: Exploring the way to improve the feasibility of seawater and sea sand. Using CLDH and CAC to improve chloride binding capacity. Molecular dynamics simulation is used for microscopic verification. Abstract: Seawater and sea sand can alleviate the shortage of resources and reduce the transportation distance of raw materials at the construction of offshore islands, whereas the high content of chloride ions in concrete mixed with seawater and sea sand induces reinforcement corrosion, which is the biggest obstacle to its wide application. This study aims to explore the way to reduce the free chloride ions content and improve the chloride binding capacity of mortar mixed with seawater and sea sand by calcined layered double hydroxide (CLDH) and alumina-rich cementitious materials (metakaolin (MK), fly ash (FA), and calcium aluminate cement (CAC)). The results show that both CLDH, MK, FA, and CAC can effectively improve the chloride binding capacity of mortar by 65%, 65%, 35%, and 200%, when the optimal dosages are 7.5%, 30%, 30%, and 100%, respectively. Moreover, molecular dynamics simulation shows that the radius correlation function (RDF) value of Cl-Ca ionic pairs is cut down at the condition that has CLDH, which reveals that the adsorption of chloride ions by CLDH occurs in the mortar is confirmed.